EFEKTIVITAS METODE SHOW AND TELL TERHADAP KEMAMPUAN BERBICARA SERTA SOSIAL EMOSIONALSISWA KELAS IV - Musarofah, Isnaeni; Iswara, Prana Dwija; Djuanda, Dadan (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
Speaking skills are an essential component of school learning that needs to be learned. In the same way, to support learning activities, students need to develop their social emotional skills. But in reality, some students still have a tough time in speaking also not able to manage their social emotional skills. This study aims to see the effectiveness of show and tell method in speaking also social emotiona skillsl. The method used was experiments with a pre-experimental research design, also used one-shot case study, one sample t-test to test the achievability of learning with minimum completion criteria and independent sample t-test to evaluate a different in speaking skills of male and female students. Fourth grade students in Bandung Regency were the subjects of this study. Based on the results of the study, the average score of students' practical speaking skills was 84.1 seen from the assessment indicators. Show and tell method was effectively used with variations in students' performance.